Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) C = 1.2 + 3.4 + 4.5 +...+ 99.100
\(\Rightarrow\) C = 1.2+2.3+3.4+4.5+...+99.100
\(\Rightarrow\)3C = 1.2.3+2.3.3+3.4.3+4.5.3+...+99.100.3
\(\Rightarrow\)3C = 1.2.3+2.3.(4-1)+3.4.(5-2)+4.5.(6-3)+...+99.100.(101-98)
\(\Rightarrow\)3C = 1.2.3+2.3.4-1.2.3+3.4.5-2.3.4+4.5.6-3.4.5+...+99.100.101-98.99.100
\(\Rightarrow\)3C = 1.2.3-1.2.3+2.3.4-2.3.4+3.4.5-3.4.5+4.5.6-4.5.6+...+99.100.101
\(\Rightarrow\)3C = 99.100.101
\(\Rightarrow C=33.100.101\)
\(\Rightarrow C=333300\)
b) D = 2 + 4 + 6 + 333 300
\(\Rightarrow\)D = 4 + 16 + 36 + 333 300
\(\Rightarrow\)D = 20 + 36 + 333 300
\(\Rightarrow\)D = 56 + 333 300
\(\Rightarrow\)D = 333 356
a, C = 1.2 + 2.3 + 3.4 + ... + 99.100
3C = 1.2.3 + 2.3.3 + 3.4.3 + .... + 99.100.3
3C = 1.2.3 + 2.3\((4-1)\)+ 3.4\((5-2)+...\)+ 99.100\((101-98)\)
3C = 1.2.3 + 2.3.4 - 1.2.3 + 3.4.5 - 2.3.4 + ... + 99.100.101 - 98.99.100
3C = 99.100.101
C = 99.100.101 :3
C = 333300
Câu b tự làm
P/S : Hoq chắc :>
Phần b mình chưa nghĩ ra
a) C = 1 . 2 + 2 . 3 + ... + 49 . 50
=> 3C = 1 . 2 . 3 + 2 . 3 . 3 + ... + 49 . 50 . 3
=> 3C = 1 . 2 . ( 3 - 0 ) + 2 . 3 . ( 4 - 1 ) + ... + 49 . 50 . ( 51 - 48 )
=> 3C = 1 . 2 . 3 - 0 . 1 . 2 + 2 . 3 . 4 - 1 . 2 . 3 + ... + 49 . 50 . 51 - 48 . 49 . 50
=> 3C = 49 . 50 . 51
=> C = 49 . 50 . 17 = 41650
Bài làm:
Ta có: \(A^2=b\left(a-c\right)-c\left(a-b\right)\)
\(A^2=ab-bc-ac+bc\)
\(A^2=ab-ac=a\left(b-c\right)\)
\(A^2=\left(-5\right).\left(-20\right)=100\)
\(\Rightarrow\orbr{\begin{cases}A=10\\A=-10\end{cases}}\)
\(B^2=c\left(a-b\right)-b\left(a-c\right)\\ B^2=ca-cb-ba+bc\\ B^2=\left(ca-ba\right)+\left(bc-bc\right)\\ B^2=a\left(c-b\right)\\ B=\sqrt{a\left(c-b\right)}\)
Thank. /ᐠ。ꞈ。ᐟ\